Metabolic syndrome: review - Bobrova, M.; Vorona, S.; Koval, S.; Savytskyi, I.; Merza, Y.; Savytskyi, V. (Journal of Education, Health and Sport, 2021)
The psychosomatic component of the metabolic syndrome, historical aspect of the problem under study, physiological and biochemical mechanisms of pathogenesis are considered in the article. The symptomatic components of the metabolic syndrome and their interrelation are outlined, the ways of diagnosis and therapy and directions of modern research in this field are outlined.